2021
DOI: 10.37934/arfmts.82.2.106119
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Flow and Heat Transfer Enhancement in A Horizontal Pipe with Plain and Dimple Twisted Tape

Abstract: In order to improve thermo-hydraulic performance of laminar flow various techniques has been used among which a plain tube with twisted tape insert is widely used. The main objective is to numerically study flow field in order to enhance heat transfer, through a circular pipe built in with/without Dimples on twisted strip. Effect of plain and dimple strip on thermo hydraulic performance discussed. The analysis results for laminar range of 800<Re<2000 is obtained with twist ratio of the strip is 3.0. Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Harish et al, [27] have been numerically investigated flow field in order to augment heat transfer, through a circular pipe built in with and without Dimples on twisted strip. And their result showed that the Dimple twisted tape and plain twisted tape tube is 4 to 15% and 3 to 12 % respectively higher than that of plain tube in terms of thermal performance factor.…”
Section: Introductionmentioning
confidence: 99%
“…Harish et al, [27] have been numerically investigated flow field in order to augment heat transfer, through a circular pipe built in with and without Dimples on twisted strip. And their result showed that the Dimple twisted tape and plain twisted tape tube is 4 to 15% and 3 to 12 % respectively higher than that of plain tube in terms of thermal performance factor.…”
Section: Introductionmentioning
confidence: 99%